A comparative study of two interventions to support reading comprehension in primary-aged students. Issue 1 (13th March 2018) - Sorrell, David; Brown, Gavin T.L.
Abstract : Purpose: The purpose of this paper is to explore the explicit teaching of information text schema with vocabulary instruction to primary-aged students in Hong Kong international education. Design/methodology/approach: Data were collected through three quasi-experimental studies with different age groups and participants. Each study divided participants into two randomly assigned groups, either informational texts (IT) or vocabulary building (VB). Impact was evaluated with gain scores on a standardized reading comprehension test and researcher-designed cloze tests of fiction and nonfiction passages. Findings: The explicit teaching of IT can benefit student reading comprehension from an early age, particularly to first language (L1) English students and possibly second language (L2) English learners. School reading programmes should include opportunities for students to experience IT (nonfiction) and fiction materials, and build their vocabulary through incidental learning and explicit teaching. For IT, they should be exposed to: layout – e.g., headings, sub-headings, glossary, and index; and content – photographs and specific/technical vocabulary. For fiction-based texts and VB, the following themes should be covered by younger aged students: antonyms, synonyms, and affixes. Research limitations/implications: Several limitations apply to this study which will need to be addressed in future studies. These include: the random sampling of students from the overall student population was not an option, given the necessity of voluntary participation and avoiding disruption to school routines. This study used meta-analysis to aggregate results across multiple comparisons largely because of the extremely small samples available. The data show large standard errors as a consequence of small numbers of participants. Hence, the current results, notwithstanding the power of meta-analysis, need to be validated with much larger samples in future studies. Originality/value: This paper suggests that greater comprehension and cloze performance among L1 students was found due to the teaching of IT compared to vocabulary training, with the reverse result for L2 English learners.